Production and Income Risk Analysis of Clove Farming in Luwu Regency - Muh. Al Aswar Rusman; Ikbal; Nur Aisyah Rusman; Muh. Ikmal Saleh (Tarjih : Agribusiness Development Journal, 2026)
Clove farming is a strategic plantation commodity contributing significantly to farmers’ income and regional economic development in Indonesia. However, this sector is characterized by high uncertainty due to climate variability, pest and disease attacks, and input limitations, which lead to production and income risks. This study aims to analyze production, income, and production risk, as well as to identify the factors affecting production risk in clove farming. The research was conducted in Luwu Regency using a survey method with purposive sampling involving 40 farmers. Data were analyzed using farm income analysis, coefficient of variation (CV) to measure production risk, and multiple linear regression to determine influencing factors. The results show that average production is 720 kg/ha/year, indicating moderate productivity, with net income reaching IDR 40,290,000/ha/year. The CV value of 0.29 reflects a moderate level of production risk, implying considerable variability in output that may affect income stability. Regression analysis reveals that land area, farming experience, labor, and fertilizer use have a negative and significant effect on production risk. These findings suggest that improving farm scale, farmer capacity, and input management is essential to enhance productivity and reduce production risk in clove farming systems.